The Quality Of Family Card Making Services At The Population And Civil Registration Office Of The Central Sulawesi Province - Setyaguna, Achmad Sholih Komara; Mustainah , Mustainah; Nasrullah, Nasrullah (Socious Journal, 2024)
This researcher sought to find out the quality of public service in the Civil Registration and Occupation Service of Central Sulawesi Province. The method used in this study is qualitatively descriptive of the number of informants of 5 people. This study uses data analysis techniques consisting of data reduction, data presentation and conclusion drawings. The results of the research showed that, the quality of public service in the Department of Occupation and Civil Registration of Central Sulawesi Province is seen from the tangible dimension (physical evidence) has already met quality of service well and provide services to the community comfortably, the dimension Reliability (Reliability) officials have been running on time according to the provisions in force and have standard procedures in performing functions as a service to the society to go with structured, the responsiveness dimension (Responsiveness) that the staff has shown attitude to the public officers will respond well and quickly, the assurance dimension (Assurance) officers in responding to completion in service is on time based on the number of people will be served if little then will be on time, the last dimension is Empathy (Empathy) that staff have shown quality of the service is by providing a sincere service, being friendly, and not discriminatory (discriminatory) so that can provide satisfaction for the community that performs the service.